MAPEAMENTO SISTEMATIZADO DA LITERATURA VISANDO A APLICAÇÃO SINÉRGICA DAS FERRAMENTAS LEAN E BIM - Falcao, Thiago; Santos, Rachel; Sousa, Lorrayne; Carvalho, Michele (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The national and international industrial building scenarios have implemented important efforts aiming better development of the sector. In this context, visual management tools are being increasingly integrated in AEC (architecture, engineering and construction) with the purpose of understanding and coordinating the information and processes in the work environment. With this sort of information, this research aims to search for articles trough the Systematic Literature Mapping (SLM) that show combined use of LEAN and BIM in the AEC industry and find gaps in this area of study. The search on Web of Science and Scopus databases returned 64 articles adherent on the theme of the study. It was observed that the study of synergy between Lean and BIM is still reduced and that the 65.53% of the articles are related to the execution phase. This study concludes that there is still a need for studies to leverage the Lean and BIM synergistically, as well as the need to develop guidelines for their uses in the design and operation and maintenance phases.